Thermotherapy for knee osteoarthritis: A protocol for systematic review. Issue 19 (14th May 2021) - Shen, Cimin; Li, Na; Chen, Bin; Wu, Jinzuan; Wu, Zhining; Hua, Dangyun; Wang, Lu; Chen, Dangdang; Shao, Zhuoyi; Ren, Changjie; Xu, Jinsen
Abstract: Background: Osteoarthritis of the knee is one of the leading causes of pain and disability among adults. Thermotherapy has been widely used to treat knee osteoarthritis. But its efficiency has not been scientifically and methodically evaluated. The aim of this study is to assess the benefits of thermotherapy for people with osteoarthritis of the knee, in terms of pain, stiffness, and physical dysfunction. Methods: Eight databases will be searched from their inception to September 2020. They are as follows: PubMed, Embase, Cochrane Library, ClinicalTrials.gov, China Knowledge Resource Integrated Database (CNKI), Weipu Database for Chinese Technical Periodicals (VIP), Chinese Biomedical Literature Database (CBM), and Wanfang Database. Two researchers will independently select studies, collect data, and assess the methodology quality by the Cochrane risk of bias tool. Results: The systematic review will provide high-quality evidence to assess the benefits and harms of thermotherapy for people with osteoarthritis of the knee, in terms of pain, stiffness, and dysfunction of knee joint, and quality of life, as well as adverse events. Conclusion: The systematic review will provide evidence to assess the effectiveness and safety of thermotherapy for knee osteoarthritis patients. INPLASY registration number: INPLASY202140038.